INVESTMENTS IN SERBIAN PIG PRODUCTION – INFLUENCE OF REGIONAL DISPARITIES - Ivanović, Sanjin; Nastić, Lana; Savić, Radomir (Economics of Agriculture, 2023)
Pig production is one of the most important elements of Serbian livestock breeding sector. Although it faces numerous challenges, there is not enough research focused on its economic effectiveness. The goal of this research is to analyze influence of regional disparities on economic efficiency of investments in Serbian pig production. The main methodological approach was to determine the present value of investments in pig production (for Mačva and Šumadija regions). Authors applied sensitivity and scenario analysis, as well. Riskiness of investments is compared using standard deviation and coefficient of variation of the expected present value. The results indicated significant influence of labor costs on net cash flows (especially in Šumadija region). Analysis revealed that (in usual circumstances) investments in pig production in Mačva region are more economically efficient. Nevertheless, rather small increase in pig price could lead to equal present values in both regions. It was determined that investments are riskier in Šumadija region.